ANALISIS BULLWHIP EFFECT MENGGUNAKAN VENDOR MANAGED INVENTORY DI UMKM MARRONE - yunitasari, elly wuryaningtyas; Wardana, Nina; Nurhayati , Emmy (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2022)
One of the problem of supply chain management is a bullwhip effect that causes less than an ideal system supply chain.. As well as UMKM Marrone, which is an industry home-based production of brownies, often experienced the bullwhip effect due to the forecasting are not properly uodated and fluctuations in demand in certain season.Â The bullwhip effect is one causes swelling of the cost of production. However, bullwhip effect can be anticipated by using a method of vendor managed inventory where the level of vendor controls both of the amount of production, distribution of the products are based on the demand of consumers.Â The result about the application of the bullwhip effect with the vendor managed inventory method based on the calculations of the BE parameter 1,15 the calculation of the BE value after and before VMI at the level of UMKM Marrone original steamed 1,17 to 0,54; double cheese 1,21 becomes 0,50, at the outlet Adiwerna original steam 1,17 become 0,56; double cheese 1,16 becomes 0,51, at outlet of Brebes orginal steam 1,17 become 0,51;double cheeseÂ 1,17 become 0,49, the outlet Mejasem original steam 1,17 become 0,52;double cheese 0,74 to 0,49,at Tegal original steam 1,16 become 0,55; double cheese 2,27 become 0,51.